The Concept of Synergy Building Awareness of State Defense in the Digital Era - Komang Redy Winatha; Putu Eka Widya Putri; Ni Made Ayu Mita Diani; Komang Permana Puspita Devi (Journal of Digital Law and Policy, 2022)
State defense has a broad spectrum in various scopes such as politics, social, economic and cultural fields. State defense and national security It is an attitude that every citizen must have. Every citizen especially the younger generation is the next generation of sustainability in the nation and state. The spirit of nationalism, patriotism, and defending the country can fade partly due to the low awareness of defending the country, not yet optimal synergy in fostering awareness of defending the country in the digital era. Seeing the current era of technology increasingly advanced, from this, the awareness of citizens, especially the younger generation in the digital era in terms of defending the country still needs to be improved, where with progress technology makes it easy for everyone to access, create or share information that is not necessarily clear. Keywords (10pt, bold): defending the country, the digital era, national resilience.